Computational investigation of the kinetics and mechanism of the initial steps of the Fischer–Tropsch synthesis on cobalt. (10th February 2017) - van Helden, Pieter; Berg, Jan-Albert van den; Petersen, Melissa A.; Janse van Rensburg, Werner; Ciobîcă, Ionel M.; van de Loosdrecht, Jan
Abstract : A multi-site microkinetic model for the Fischer–Tropsch synthesis (FTS) reaction up to C2 products on a FCC cobalt catalyst surface is presented. This model utilizes a multi-faceted cobalt nanoparticle model for the catalyst, consisting of the two dominant cobalt surface facets Co(111) and Co(100), and a step site represented by the Co(211) surface. The kinetic parameters for the intermediates and transition states on these sites were obtained using plane-wave, periodic boundary condition density functional theory. Using direct DFT data as is, the microkinetic results disagree with the expected experimental results. Employing an exploratory approach, a small number of microkinetic model modifications were tested, which significantly improved correspondence to the expected experimental results. Using network flux and sensitivity analysis, an in-depth discussion is given on the relative reactivity of the various sites, CO activation mechanisms, the nature of the reactive chain growth monomer, the probable C2 formation mechanism, the active site ensemble interplay and the very important role of CO* surface coverage. The findings from the model scenarios are discussed with the aim of guiding future work in understanding the FTS mechanism and subsequent controlling kinetic parameters.